Distinguishing between isomeric neoxanthin and violaxanthin esters in yellow flower petals using liquid chromatography/photodiode array atmospheric pressure chemical ionization mass spectrometry and tandem mass spectrometry. (30th June 2021) - Watanabe, Takehiro; Yamagaki, Tohru; Azuma, Toshiaki; Horikawa, Manabu
Abstract : Rationale: Liquid chromatography/photodiode array atmospheric pressure chemical ionization mass spectrometry (LC/PDA‐APCI‐MS) is used for the analysis of various carotenoid pigments in plants. Among them, it is difficult to distinguish between the isomeric violaxanthin/neoxanthin esters. Methods: The yellow pigments of tomato petals were extracted with acetone, and the extracts were kept at −30°C to allow the contaminating triacylglycerols to settle out physically. The supernatants were analyzed using LC/PDA‐APCI‐MS with a high‐resolution orbitrap mass spectrometer for their exact masses. The expected carotenoid esters were calculated with the combination of carotenoids and fatty acids, and they were matched with the experimental exact masses. The fatty acid structures in the carotenoid esters were also identified using collision‐induced dissociation (CID) tandem mass spectrometry (MS/MS). The isomeric violaxanthin/neoxanthin esters were distinguished using CID MS/MS from their in‐source dehydrated product ions as pseudoprecursor ions. Results: The in‐source dehydrated ions [M − H2 O + H] + of neoxanthin diesters predominated over their protonated molecules [M + H] + in LC/MS. By contrast, the protonated molecules of violaxanthin diesters predominated. The 92 u loss product ions [M − H2 O − C7 H8  + H] + were observed from the dehydrated violaxanthin diesters, but they were not generated from the dehydrated neoxanthin diesters in the CID MS/MS of their dehydrated pseudoprecursor ion [M − H2 O + H] + . Conclusions: The allene allyl carbocation in neoxanthin diesters was generated from dehydration after preferential protonation at the hydroxy group. The epoxide group of violaxanthin diesters opens easily after protonation; however, the dehydration did not proceed at this stage. The 92 u loss of C7 H8 was explained by an intramolecular [2 + 2] cycloaddition, which proceeded preferentially in dehydrated violaxanthin diesters because the carbocations in the dehydrated species were conjugated to the polyene and those double bonds were depolarized during CID MS/MS. Therefore, the isomeric neoxanthin/violaxanthin diesters were distinguished using LC/PDA‐APCI‐MS and MS/MS. This method was a practical and useful method of profiling the carotenoid esters of the yellow petals.